1997
DOI: 10.1590/s1020-49891997000100003
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory illnesses in the first 18 months of life

Abstract: To help assess the causes and frequency of acute respiratory illnesses (ARI) during the first 18 months of life in Chile, a cohort of 437 children born in good health between May 1991 and April 1992 was followed at an urban health clinic in northern Santiago. Information was obtained from medical checkups performed at the clinic, from emergency health care services, from private physicians, and from interviews with each child's mother when the child was enrolled in the study and when it was 6, 12, and 18 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 3 publications
(6 reference statements)
0
12
0
1
Order By: Relevance
“…Rylander et al found a significant relationship between tobacco smoke exposure and wheezing among infants up to 18 months of age 17 . Tobacco smoke exposure is considered among the risk factors of pneumonia 18–20 …”
Section: Discussionmentioning
confidence: 99%
“…Rylander et al found a significant relationship between tobacco smoke exposure and wheezing among infants up to 18 months of age 17 . Tobacco smoke exposure is considered among the risk factors of pneumonia 18–20 …”
Section: Discussionmentioning
confidence: 99%
“…In several studies finding no association, relatively small proportions of the samples were exposed. Thus, in urban Brazil only 6% of children were exposed to indoor smoke (Victora et al, 1994) and in another south American study 97% of homes used gas for cooking, although 81% used polluting fuels (kerosene, wood, coal) for heating (Lopez-Bravo et al, 1997). This study also excluded neonates with birth weight <2,500 gms -the group most vulnerable to ALRI.…”
Section: Acute Lower Respiratory Infectionsmentioning
confidence: 97%
“…Five studies reported no significant association between ALRI incidence and exposure (Johnson & Aderele, 1992;Victora et al, 1994;Shah et al, 1994;Wesley & Loening, 1996, Lopez-Bravo et al, 1997, but the remainder reported significantly elevated ORs (for incidence or deaths) in the range 2-8. Not all however, have dealt adequately with confounding factors (Pandey te al., 1989;Kossove, 1982;Cerquiero et al, 1990;Collings et al, 1990;Johnson & Aderele, 1992), although accounting for confounding in studies of this exposure may in any case be problematic (Armstrong & Campbell, 1991;Bruce et al, 1998).…”
Section: Acute Lower Respiratory Infectionsmentioning
confidence: 99%
See 2 more Smart Citations